Essay Error Analysis on the 1st Year Students of English Education Department - Mustakim, Mustakim; Samad, Ita Sarmita (Universitas Muhammadiyah Enrekang, 2019)
Analyzing student problems is very important part to help English teachers in developing teaching materials, assessments and teaching methods. Unfortunately, this is not a very easy thing unless the teacher has to analyze student errors. This study discussed common mistakes made by STKIP Muhammadiyah Enrekang students in the first year in writing Essay. Qualitative descriptive research was used to describe data relating to errors used in essay writing on first year of English department of STKIP Muhammadiyah Enrekang. In this paper, researchers discussed the research method namely (1) research design, (2) subject and object of research, (3) method and data collection instruments, and (4) data analysis. The data obtained from assignments collected which have been given for several weeks. Types of errors can be classified into 24 types out of 10 mistakes of students’ essay writing from the highest to the lowest. They are article, preposition, spelling, word choice, subject-verb agreement, auxiliary verb, plural form, verb form, capital letter, and meaningless sentences.